Genome Mining Approach Reveals the Occurrence and Diversity Pattern of Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-Associated Systems in Lactobacillus brevis Strains - Panahi, Bahman; Majidi, Mohammad; Hejazi, Mohammad Amin (Frontiers in Microbiology, 2022)
Clustered regularly interspaced short palindromic repeats (CRISPR) together with their CRISPR-associated (Cas) genes are widely distributed in prokaryotes that provide an adaptive defense mechanism against foreign invasive DNA. There is relatively little knowledge about the CRISPR-Cas diversity and evolution in Lactobacillus brevis strains. Therefore, in this study, a genome-mining approach was employed to investigate the diversity and occurrence of the CRISPR-Cas system in 83 L. brevis strains. Moreover, trans-activating CRISPR (tracrRNA) and protospacer adjacent motif (PAM) as pivotal elements for the successful targeting and inference of phages by the subtype II CRISPR-Cas systems were surveyed. Finally, evolutionary paths of L. brevis strains under selective pressure from foreign invasive DNA such as plasmids and phages of studied strains were surveyed using acquisition and deletion events analysis of spacers. A total of 127 confirmed CRISPRs were identified, which were distributed in 69 strains. Among strains with confirmed CRISPRs, 35 strains only contained one CRISPR locus, 23 strains contained two CRISPR loci, and 12 strains contained three to six CRISPR loci. L. brevis strains frequently harbor more than one CRISPR system. Analysis of confirmed CRISPR arrays showed that 31 out of 127 confirmed CRISPRs included Cas genes which were categorized as one of the II-A, II-C, and I-E subtypes. Analysis of subtype II-A spacers reflected divergent evolution for 18 strains into 16 unique groups. Additional analysis of spacer sequences also confirmed the implication of characterizing CRISPR-Cas systems in targeting of phages and plasmids. The current study highlighted the potential of utilizing CRISPR spacer polymorphism in genotyping lactobacillus strains. Moreover, it provides deep insights into the occurrence, diversity, and functional impacts of the CRISPR-Cas system in L. brevis strains.